The Relationship between Teachers' Spatial Job Stability and Job Performance: An Analytical Field Study in Muscat Governorate Schools in the Sultanate of Oman - Al-Baluoshi, Mohammed Suleiman (Journal of Educational and Psychological Sciences, 2025)
The work environment and spatial job stability are critical determinants in shaping teachers’ performance and enhancing the overall quality of the educational system. This study aims to analyze the relationship between spatial job stability and the job performance of teachers in schools across Muscat Governorate, Sultanate of Oman, while also examining differences based on demographic variables such as gender, years of experience, educational level, and marital status. The study adopted the descriptive-analytical approach, appropriate for the nature of non-experimental variables, and utilized a validated questionnaire as the primary data collection tool, covering two main dimensions: spatial job stability and professional performance.
Keywords: Spatial job stability; job performance; teacher; education; organizational environment